Greenovation and Planting Class: Collaborative Greenhouse Development and Planting Education for Village Food Self-Sufficiency - Ni'matul Izza; Rafael Hario Rivandi; Latifah Maharani; Septira Arshiana; Irvan Shofiyanto; Salma Azizah Asy Syahidah (Jurnal Masyarakat Madani Indonesia, 2026)
Pagentan Village is characterized by high population density and extensive land conversion into residential areas, resulting in limited agricultural land and green open spaces. This condition weakens local food security and limits practice-based environmental education, particularly at the elementary school level. In response, the “Village Greenovation and Planting Class” program was implemented to promote community empowerment and environmental education. The program involved residents of RT 06 RW 04 and students of MI Al-Ma’arif 02 Pagentan through activities such as the construction of an eco-friendly greenhouse, training in sustainable agricultural practices, and the integration of planting activities into thematic learning. The program aimed to strengthen food security through collaborative greenhouse management, enhance community capacity in environmentally friendly cultivation techniques, and instill environmental awareness and independence among students from an early age. The implementation results showed increased community knowledge and skills in sustainable agriculture, optimized use of limited land, and greater student participation in environment-based learning. Through collaboration between the local community and the school, the program successfully developed a greenhouse for independent food production while fostering environmental values and sustainable farming skills.